Encyclopedia of business information sources : a bibliographic guide to approximately 22,000 citations covering more than 1,100 primary subjects of interest to business personnel - Woy, James B. (Gale Research Company, 1986)
includes : abstract services and indexes, almanacs and yearbooks, bibliographies, bibliographical services, directories, encyclopedias and dictionaries, financial ratios, handbooks and manuals, Online Data Bases, Periodicals and Newsletters, Price Sources, Research Centers and Institutes, Statistics Sources, Trade Associations and Professional Societies, and Other Sources of Information on Each Topic.